Intravenous Foscarnet With Topical Cidofovir for Chronic Refractory Genital Herpes in a Patient With AIDS - Agnes Usoro BSN; Alfreda Batts BS; Juan C. Sarria MD (SAGE Publishing, 2015)
Few case reports have documented the use of topical cidofovir for refractory genital herpes simplex virus (HSV) ulcers in human immunodeficiency virus (HIV) infected patients. This drug formulation lacks a standardized concentration or even a procedural outline as to how it should be compounded. We aim to discuss the utilization of topical cidofovir in addition to presenting a procedural means of compounding it for treatment of refractory genital HSV ulcers. Our patient completed 21 days of intravenous foscarnet and 13 days of topical cidofovir with clinical improvement in the penile and scrotal ulcers. Genital herpes is a concern in patients with HIV because it generally manifests as a persistent infection. Physicians should be aware that when patients fail to respond to the conventional treatment regimens for genital HSV in a timely manner, other options are available, such as topical cidofovir as an adjuvant to systemic antivirals.